Tapping into museums for art psychotherapy: an evaluation of a pilot group for young adults. Issue 3 (3rd July 2018) - Coles, Ali; Harrison, Fiona
ABSTRACT: This article describes a pilot museum-based art psychotherapy group for seven 18 to 25-year-old adults with severe mental health difficulties. We outline existing evidence for the psychotherapeutic value of museums and describe how we tried to harness the potential of museums as socially inclusive, accessible and inspiring venues, as well as a rich source of encounters with objects and environments which can mobilise introspection and meaning-making. We explain how we evaluated the group in order to assess therapeutic outcomes and the contribution of the museum setting to these, using quantitative data from outcome measures and qualitative data from the therapy sessions and post-therapy reflective interviews. Overall, the data suggested that the therapy group was beneficial to participants. The young adults reported that the museum setting helped them to reflect on feelings and experiences, facilitated interaction between group members, encouraged independence, fostered motivation and creativity and helped them to feel valued and connected with the world outside mental health services. These evaluation findings are an encouragement to other art psychotherapists to consider tapping into the therapeutic benefits of this rich cultural resource.